A new Holocene sea-level record for Singapore. (September 2021) - Chua, Stephen; Switzer, Adam D; Li, Tanghua; Chen, Huixian; Christie, Margaret; Shaw, Timothy A; Khan, Nicole S; Bird, Michael I; Horton, Benjamin P
Relative sea-level (RSL) records from far-field regions distal from ice sheets remain poorly understood, particularly in the early Holocene. Here, we extended the Holocene RSL data from Singapore by producing early Holocene sea-level index points (SLIPs) and limiting dates from a new ~40 m sediment core. We merged new and published RSL data to construct a standardized Singapore RSL database consisting of 88 SLIPs and limiting data. In the early Holocene, RSL rose rapidly from −21.0 to −0.7 m from ~9500 to 7000 cal. yrs. BP. Thereafter, the rate of RSL rise decelerated, reaching a mid-Holocene highstand of 4.0 ± 4.5 m at 5100 cal. yrs. BP, before falling to its present level. There is no evidence of any inflections in RSL when the full uncertainty of SLIPs is considered. When combined with other standardized data from the Malay-Thai Peninsula, our results also show substantial misfits between regional RSL reconstructions and glacial isostatic adjustment (GIA) model predictions in the rate of early Holocene RSL rise, the timing of the mid-Holocene highstand and the nature of late-Holocene RSL fall towards the present. It is presently unknown whether these misfits are caused by regional processes, such as subsidence of the continental shelf, or inaccurate parameters used in the GIA model.